Problem-Oriented Student Worksheet based Learning: Cultivating Creativity in Primary School Students - Setyaningsih, Hana Ilvi; Sutama, S (Universitas Muhammadiyah Surakarta, 2023)
Education today is geared towards developing 21st-century skills. One of the skills that needs to be developed is creativity. The objectives of this research are: (1) to describe the use of problem-based learning-oriented student worksheets for grade 4 students at Kasinoman 3 State Elementary School; and (2) to explore the cultivation of creativity in grade 4 students at Kasinoman 3 Elementary School. The general type of research is research and development. Meanwhile, the type of research in this article is ethnographic qualitative research. This research was conducted at Kasinoman 3 Elementary School in August 2023. The subjects of this research were 11 fourth-grade students. Data collection techniques are carried out through observation, interviews, and documentation. The credibility test is used to test the validity of the data obtained. The data analysis technique was carried out using the Allure method. The results of the research show that the use of student worksheets oriented towards problem-based learning.